Implementasi Sister City dalam Menanggulangi Isu Lingkungan Hidup: Studi Kasus Kendari dan La Rochelle (Global Focus, 2022)
The purpose of this research was to determine the form of sister city cooperation carried out by the Kendari City Government and Communauté D'Angglomération De La Rochelle in 2015-2018. This research uses qualitative research methods, by collecting data and information from sources through interviews and literature study. The results indicate a form of collaboration carried out by the Kendari City Government and Communauté D'Angglomération De La Rochelle, namely the exchange of information in the form of sending experts and training. In clean water services field, the form of cooperation was to increase the production and network of drinking water in the Kendari City area by carrying out a pilot project for the provision of drinking water for 24 hours / day and can be drunk immediately. In the city hygiene management field, the form of cooperation focused on sorting and managing waste in Kendari City. From the sister city collaboration, there were increasement in the experts’ skill and knowledge in Kendari City.